Impact of birth complication and early medical illness on cognitive abilities and academic attainment of children and adolescents - Parvin, Mst Afroza; Islam, Shaheen (Dhaka University Journal of Biological Sciences, 2013)
The study focused on birth complication and early medical illness as detrimental developmental factors having adverse impact on children and adolescents’ cognitive abilities and academic attainment. To assess cognitive abilities Wechsler Intelligence Scale for Children - Fourth edition (WISC-IV) was administered on 44 (26 boys, 18 girls) students of primary and secondary level schools of Dhaka city. The performance of last two consecutive school examinations was taken as a measure of academic attainment. The results revealed that higher percentages of students who had serious medical illness during early childhood demonstrated poor academic attainment. It has also revealed significant difference in students’ working memory as well as verbal working memory in terms of academic achievements and serious medical illness during childhood. The results of this study have implications for early screening of children with developmental risk factors for early identification of possible poor cognitive abilities and poor academic attainment. Dhaka Univ. J. Biol. Sci. 22(2): 109-117, 2013 (July)